2011
DOI: 10.1186/1479-5876-9-30
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-205 modulates cellular invasion and migration via regulating zinc finger E-box binding homeobox 2 expression in esophageal squamous cell carcinoma cells

Abstract: BackgroundEsophageal squamous cell carcinoma (ESCC) is often diagnosed at later stages until they are incurable. MicroRNA (miR) is a small, non-coding RNA that negatively regulates gene expression mainly via translational repression. Accumulating evidence indicates that deregulation of miR is associated with human malignancies including ESCC. The aim of this study was to identify miR that could be specifically expressed and exert distinct biological actions in ESCC.MethodsTotal RNA was extracted from ESCC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 38 publications
6
104
0
Order By: Relevance
“…Cellular senescence should be viewed as a general cellular stress response program that can be activated by the cell when coordinately exerts tumor-suppressor activities with the miR-200 family to inhibit EMT, 72,[78][79][80] was also markedly upregulated in HDFs that have undergone SIS in response to metformin (Fig. 4A).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular senescence should be viewed as a general cellular stress response program that can be activated by the cell when coordinately exerts tumor-suppressor activities with the miR-200 family to inhibit EMT, 72,[78][79][80] was also markedly upregulated in HDFs that have undergone SIS in response to metformin (Fig. 4A).…”
Section: Discussionmentioning
confidence: 99%
“…Given the well-described role of miR-205 in EMT pathways, [34][35][36] we investigated the effects of miR-205 overexpression on EMT family members and demonstrated a connection between miR-205 overexpression and an associated reduction of ZEB2 mRNA and protein levels with a reciprocal increase on E-cadherin mRNA and protein levels. Re-introduction of ZEB2 into 1205Lu melanoma cells overexpressing miR-205 rescues the observed defects in cell migration and invasion and restores suppression of E-cadherin.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] As miR-205 expression is progressively diminished from nevi to primary melanomas to metastatic melanomas and because enforced expression of miR-205 impairs melanoma cell mobility, we hypothesized that miR-205 expression might impact ZEB1/2 and consequently, E-cadherin expression in melanoma cells. As shown in Figure 5a, we established a panel of cell lines representing all stages of melanoma progression: WM35 (radial growth phase only), WM793 (vertical growth phase primary melanoma), WM115A (metastatic melanoma) and 1205Lu (metastatic melanoma) stably expressing relatively similar levels of (Figure 5a).…”
Section: Effects Of Mir-205 Overexpression In Vivomentioning
confidence: 99%
“…As another mechanism of tumor suppression by miR-205, Dar et al (2011) reported that miR-205 suppressed cell proliferation by regulating the E2F1 protein in melanoma cells. In addition, Matsushima et al (2011) examined the role of miR-205 in inhibiting cellular invasion and migration in esophageal squamous carcinoma. Interestingly, Majid et al (2010) showed that a new functional mechanism of miR-205 specifically activates tumor suppressor genes, such as interleukin-24 (IL-24) and interleukin-32 (IL-32), by targeting specific sites in their promoters.…”
Section: Introductionmentioning
confidence: 99%